High Spectrum Efficiency and Low BER of Massive MIMO System using Spectrum Sensing Cognitive Radio Network - Dubey, Rishika; Nigam, Vineeta Saxena (International Journal of Computer Sciences and Engineering, 2019)
In a cellular network, the demand for high throughput and reliable transmission is increasing in large scale. One of the architectures proposed for 5G wireless communication to satisfy the demand is Massive MIMO system. The massive system is equipped with the large array of antennas at the Base Station (BS) serving multiple single antenna users simultaneously i.e., number of BS antennas are typically more compared to the number of users in a cell. This additional number of antennas at the base station increases the spatial degree of freedom which helps to increase throughput, maximize the beamforming gain, simplify the signal processing technique and reduces the need of more transmit power. The advantages of massive MIMO can be achieved only if Channel State Information (CSI) is known at BS uplink and downlink operate on orthogonal channels. The studied of non-cooperative cognitive radio network based massive MIMO systems is present in this paper.